2015
DOI: 10.18632/oncotarget.5174
|View full text |Cite
|
Sign up to set email alerts
|

A cytoplasmic C-terminal fragment of syndecan-1 is generated by sequential proteolysis and antagonizes syndecan-1 dependent lung tumor cell migration

Abstract: Syndecan-1 is a surface expressed heparan sulphate proteoglycan, which is upregulated by several tumor types and involved in tumor cell migration and metastasis. Syndecan-1 is shed from the cell surface and the remaining transmembrane fragment undergoes intramembrane proteolysis by γ-secretase. We here show that this generates a cytoplasmic C-terminal fragment (cCTF). In epithelial lung tumor A549 cells the endogenously produced cCTF accumulated when its proteasomal degradation was blocked with bortezomib and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
0
20
0
1
Order By: Relevance
“…Although the notch transcriptional target HEY1 was downregulated by GSI treatment in our cell models, we cannot exclude that additional targets of GSI were regulated in our study. For example, cell surface receptors of the syndecan family, which act as regulators of invasive growth in endometriosis, have been shown to be sensitive to GSIs . Additional caveats are associated with a potential clinical application of GSIs in an endometriosis setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the notch transcriptional target HEY1 was downregulated by GSI treatment in our cell models, we cannot exclude that additional targets of GSI were regulated in our study. For example, cell surface receptors of the syndecan family, which act as regulators of invasive growth in endometriosis, have been shown to be sensitive to GSIs . Additional caveats are associated with a potential clinical application of GSIs in an endometriosis setting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cell surface receptors of the syndecan family, which act as regulators of invasive growth in endometriosis, 3,33 have been shown to be sensitive to GSIs. 34 Additional caveats are associated with a potential clinical application of GSIs in an endometriosis setting. These include possible fertility-related side effects linked to a downregulation of LIFR, a possible angiogenesis-promoting effect of some GSIs, 11 and gastrointestinal side effects previously reported in clinical trials on GSIs.…”
Section: Discussionmentioning
confidence: 99%
“…This is another study, to some extent, underlines the inhibitory role of CD98 activity. Moreover, syndecan-1 cCTF (cytoplasmic C-terminal fragment) antagonizes syndecan-1 dependent tumor cell migration by competing with the full length syndecan-1 for intracellular interaction partners and thereby reduces signaling of syndecan-1 [33]. There may be some mechanisms, from the perspective of single molecules, for maintaining cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The C‐terminal Sdc1 fragment suppressed tumour cell migration and increased basal phosphorylation of Src and FAK. The authors explain the observed effects with an antagonizing mechanism of the C‐terminal fragment for the Sdc1‐dependent tumour cell migration in vitro and in vivo by dysregulating pro‐adhesive signalling pathways (Pasqualon et al ., ).…”
Section: Current Therapies Targeting Syndecansmentioning
confidence: 97%